Lipases: From Production to Applications. Issue 2 (2nd April 2020) - Melani, Natália B.; Tambourgi, Elias B.; Silveira, Edgar
Abstract : Lipases (triacylglycerol hydrolases E.C. 3.1.1.3) are enzymes produced by mammals, plants, fungi and bacteria that catalyze the hydrolysis of triacylglycerols into glycerol and fatty acids. Lipases are versatile in lipid biotechnology due to their selective properties, which have been applied in recent years in emulsifiers, pharmaceuticals, cosmetics, flavors, fragrances, as well as for the pretreatment of lipid-rich wastewater, the bioremediation of oils and biodiesel synthesis. This review offers information collected over the last 10 years on lipase sources as well as advances in production, purification strategies and the main applications in industry.